Abnormal nuchal translucency followed by normal microarray analysis is associated with placental pathology‐related complications. (25th January 2021) - Krispin, Eyal; Kushnir, Anya; Shemer, Asaf; Rienstein, Shlomit; Berkenstadt, Michal; Yinon, Yoav; Weisz, Boaz
Abstract: Objective: Identify placental pathology‐related complications, labor and neonatal outcomes in pregnancies complicated by pathological nuchal translucency (NT) with normal microarray analysis. Methods: A retrospective study in which all women with singleton pregnancy who demonstrated NT above 3 mm and a normal microarray analysis were matched to women with normal NT and a normal microarray analysis (2013–2019) in a single tertiary academic center. The following placental pathology‐related parameters were measured: preeclampsia, oligohydramnios, suspected intrauterine growth restriction, abnormal Doppler studies or small for gestational age (SGA) neonates. The primary outcome was defined as a composite of complications related to placental pathology including preeclampsia and SGA neonate. Secondary outcomes were labor complications and neonatal morbidity. Results: A total of 185 women were included in the study: of them, 47 presented an abnormal NT (study group) and 138 presented normal NT (controls). Groups did not significantly differ in baseline characteristics. Regarding primary outcome, all placental‐related complications frequencies were higher in the study group, with a composite rate of 17.02% versus 6.52% in controls ( p = 0.042%). Secondary outcomes did not differ between groups. Conclusions: Abnormal NT measurement presented in pregnancies with normal fetal microarray analysis is associated with higher rates of placental‐related complications. Key Points: What's already known about this topic? Pathological NT is considered to be related to genetic anomalies. What does this study add? Pregnancies with increased nuchal translucency and no chromosomal anomalies using microarray analysis are associated with an increased risk for placental‐related disorders. Practitioners should consider such pregnancies as high risk, and proper counseling should be given to the parents.